STRATEGI GURU DALAM MEMBINA KEMAMPUAN DASAR MENGENAL HURUF HIJAIYYAH MELALUI PENDEKATAN CONTEXTUAL LEARNING PADA KELAS A PAUD JANNATUL HAZNI DUSUN TONTONG SUIT DESA BAGEK PAPAN - Khairul Huda, Nurul Iman dan Sabahiyah (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2022)
The purpose of this community service is to trainning the teachers in Teacher Strategy on Fostering Basic Ability to Recognize Hijaiyyah Letters through Contextual Learning Approach at PAUD Jannatul Hazni Tontong Suit Village Bagik Papan, East Lombok. This is based on the lack of experience and skills of teachers in developing contextual approach strategies. The specific target achieved from this training activity is to provide reinforcement and improve teacher skills in using a contextual learning approach strategy in fostering basic skills on recognizing hijaiyyah letters. The method is used participatory training and mentoring. all teachers in the institution become training participants in community service. The implementation of community service activity includes by providing material on the teacher's strategy in using the contextual learning approach. It has been done as a form of strengthening and ability of teachers in implementing contextual learning approach strategies. After conceptual strengthening, the teacher provides intensive assistance in evaluation practice based on standardized program evaluation mechanisms starting from selecting programs to be evaluated, formulating goals, determining the evaluation model used, developing instruments, collecting data, and analyzing data from program evaluation results. To maintain the sustainability of the results of this activity, mentoring continues to be carried out between the teacher and the Service Implementation Team so that the objectives of the implementation of this community service activity can be achieved optimally.